2017
DOI: 10.1038/s41559-017-0123
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization erodes ectomycorrhizal fungal diversity and may cause microbial communities to converge

Abstract: Urbanization alters the physicochemical environment, introduces non-native species and causes ecosystem characteristics to converge. It has been speculated that these alterations contribute to loss of regional and global biodiversity, but so far most urban studies have assessed macro-organisms and reported mixed evidence for biodiversity loss. We studied five cities on three continents to assess the global convergence of urban soil microbial communities. We determined the extent to which communities of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
88
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 42 publications
9
88
3
Order By: Relevance
“…An equalizing effect of disturbance on levels of AM fungal alpha diversity is also consistent with recent findings on other microbes (ectomycorrhizal fungi, archaea and bacteria; Epp Schmidt et al, 2017) that reported biotic homogenization resulting from biodiversity loss in some communities, but not others. Our currently limited knowledge about the distribution and ecology of AM fungal taxa makes it difficult to specify mechanisms underlying the selection of functional traits that might drive equalization of diversity levels.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…An equalizing effect of disturbance on levels of AM fungal alpha diversity is also consistent with recent findings on other microbes (ectomycorrhizal fungi, archaea and bacteria; Epp Schmidt et al, 2017) that reported biotic homogenization resulting from biodiversity loss in some communities, but not others. Our currently limited knowledge about the distribution and ecology of AM fungal taxa makes it difficult to specify mechanisms underlying the selection of functional traits that might drive equalization of diversity levels.…”
Section: Discussionsupporting
confidence: 90%
“…However, as suggested by Epp Schmidt et al. (), a mechanism analogous to that influencing plants (i.e. the exclusion of an important number of late successional specialist species from naturally rich communities, which is compensated in naturally poor communities by the arrival of new pioneer species) may also influence these soil organisms.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…First, urban locations were found, for our analyses utilizing a 50‐km 2 grid, exclusively at lower latitudes. Consistent with previous research (Schmidt et al., ), mean diversity in urban systems was reduced for both fungal nutritional modes (Fig. ), with greater negative impacts to ectomycorrhizal fungal diversity in urban systems compared to forests (Appendices ).…”
Section: Discussionsupporting
confidence: 89%